KISHI JASTAǴÍ BALALARDÍŃ KÓRKEMLIK XÍZMETIN RAWAJLANDÍRÍWDA ERTEKLERDIŃ ÁHMIYETI - Ibragimova, L. (SCIENCE and SOCIETY, 2020)
The article discusses the role of fairy tales in the development of the artistic perception of young children. The history of fairy tales is briefly described, their role in the life of children, examples from fairy tales are given.